Os nervos periféricos e suas alterações neoplásicas - Viott, Aline de Marco (2006)
A review on the peripheral nervous system (PNS) with emphasis on Schwann cells and neoplastic lesions of the system was performed. Schwann cells functions during PNS development as well as their importance during repair of nerve fibers and myelin within the nervous system were approached. Literature review points to numerous functions of Schwann cells and to new growth factors and genes that influence PNS development. A retrospective study of PNS tumors was made from the files of the Veterinary Pathology Laboratory of the Federal University of Santa Maria, Brazil, between 1964 and 2004. Peripheral nerve tumors summed up 12, 7 schwannomas and 5 neurofibromas. From those, 9 were studied from their clinical and macroscopical aspects, and histologically by histochemistry and immunohistochemistry. Histological features as neoplastic cell type, shape, cell differentiation, mitotic index, atypic cellular changes, encapsulation, eoplastic cells infiltration on surrounding tissues, edema, hemorrhage, necrosis, and inflammation were evaluated. Masson´s trichrome and Picrosírius red staining methods heightened connective tissue components that were more prevalent in neurofibromas with a characteristic deployment of collagens I and III. In AgNOR techniques both benign and malignant schwannomas and neurofibromas did not show significant statistic differences. Mast cells stained by toluidine blue were more prevalent in neurofibromas which are rich in reactive endoneurium. Schwannomas (100%) and nurofibromas (100%) were positive for vimentin and S100 protein, so they prove to be reliable for the diagnosis of PNS tumors. GFAP marked cells were randomly found within schwannomas and Schwann cells within neurofibromas, and this labelling must be used together with other techniques to reach and accurate diagnosis.